Reading gender in Judges: an intertextual approach - Birdsong, Shelley L.; Vos, Jacobus Cornelis de; Kim, Hyun Chul Paul (Resources for biblical study, 2023)
"Much of the content of Judges can be understood only when read together with other parts of the Hebrew Bible. Narratives in Judges comment, criticize, and reinterpret other texts from across what became the canon, often by troubling gender, disrupting stereotypical binaries, and creating a kind of gender chaos. This volume brings together gender criticism and intertextuality, methods that logically align with intersectional lenses, to draw attention to how race, ethnicity, class, religion, ability, sex, and sexuality all play a role in how one is gendered in the book of Judges. Contributors also draw on theology, ancient and contemporary culture, and reception history to read gender in Judges"--